2006
DOI: 10.1002/ijc.21770
|View full text |Cite
|
Sign up to set email alerts
|

A p21/WAF1 mutation favors the appearance of drug resistance to paclitaxel in human noncancerous epithelial mammary cells

Abstract: We investigated the mechanisms responsible for paclitaxel resistance in HME-1 cells (human mammary epithelial cells immortalized with hTERT). These cells were exposed to paclitaxel (10 pM for 7 days) and 20 cellular surviving populations (PSP) were obtained. PSP demonstrated high levels of resistance to paclitaxel cytotoxicity as compared with HME-1 cells. Activation of mdr-1 gene expression was observed in 2 PSP. Protein expression analysis using a C-terminal targeted antibody showed that 13 PSP were negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Selective screening of patient DNA was performed as determined by its corresponding homozygosity profile. Mutation analysis was carried out by PCR-direct sequence analysis of selected regions of protein tyrosine phosphatase, non-receptor type 11 (PTPN11) (exons 3 and 13); 26 histone H4 (HIST1H4D), Splicing factor, arginine/serine-rich 3 (SFRS3), cyclin-dependent kinase inhibitor 1A (CDKN1A/p21 WAF1/CIP1 ), 27 cyclin D3 (CCND3) and cyclin-dependent kinase inhibitor 2A (CDKN2A) were all screened in their entirety. Tumour protein 53 (TP53) screening of this series has been published previously.…”
Section: Mutation Analysismentioning
confidence: 99%
“…Selective screening of patient DNA was performed as determined by its corresponding homozygosity profile. Mutation analysis was carried out by PCR-direct sequence analysis of selected regions of protein tyrosine phosphatase, non-receptor type 11 (PTPN11) (exons 3 and 13); 26 histone H4 (HIST1H4D), Splicing factor, arginine/serine-rich 3 (SFRS3), cyclin-dependent kinase inhibitor 1A (CDKN1A/p21 WAF1/CIP1 ), 27 cyclin D3 (CCND3) and cyclin-dependent kinase inhibitor 2A (CDKN2A) were all screened in their entirety. Tumour protein 53 (TP53) screening of this series has been published previously.…”
Section: Mutation Analysismentioning
confidence: 99%
“…Paclitaxelsurviving populations were obtained from HME1 cells as reported previously (Galmarini et al, 2006). Briefly, HME1 cells were seeded onto 20 separate 96-well plates at a concentration of 100 cells/well.…”
Section: Obtention Of Pspsmentioning
confidence: 99%
“…These assays were carried out without the use of specific markers of chromosomes, and thus estimated the global missegregation process but did not specify associated chromosome aberrations (for example, nucleoplasmic bridges, chromosome non-disjunction and breakage). We decided to test effects of 1 and 20 nM paclitaxel on chromosome segregation, as these two doses were previously found to be the paclitaxel IC 20 and IC 80 in HME1 cell line (Galmarini et al, 2006). Moreover, these doses act differentially to induce cell death in untransformed mammary cells.…”
Section: Paclitaxel Induces Persistent Chromosome Missegregation In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The authors reported a point mutation in exon 2 of the p21 gene (WAF1, CIP1, CDKN1A), leading to a premature STOP in codon 127 and paclitaxel resistance in noncancerous epithelial breast cells. The cyclin-dependent kinase inhibitor p21 is a main effector of growth arrest induced by p53.…”
mentioning
confidence: 99%